MORPHOLOGICAL CHARACTERIZATION OF PROMISING GUAVA (PSIDIUM GUAJAVA L.) VARIETIES UNDER SUB-TROPICAL HUMID CONDITIONS OF NORTH INDIA - SINGH, DHARMENDRA; GILL , M. I. S.; ARORA, N. K. (The Bioscan, 2016)
The morphological studies on the performance of different guava varieties revealed that the tree height was medium (2 to 4 m) in Pant Prabhat, Arka Amulya, Shweta and Thailand.Red coloured young shoots (Anthocyanin colouration) were observed in Allahabad Safeda, Punjab Pink, L-49, Lalit, Shweta, Pear Shaped.A significant variation in leaf length was observed among different guava varieties ranging from 101.89 mm in Lalit to 151.27 mm in Punjab Pink,while, maximum leaf blade width was recorded in the variety L-49 (65.54 mm). Leaf chlorophyll index values ranged from 38.60 to 51.70 with an overall mean value of 42.84 with the maximum chlorophyll index in variety Pear Shaped. First sign of flower bud for winter season crop was noted from 21st to 25th June. In winter season crop, variety Punjab Pink was first to have open flower on 5th July. Maximum mean flower size (47.01 mm) for winter season crop was recorded in L-49. Varieties Hisar Safeda (42 days), 17-16, Lalit, G.Bilas and Pear Shaped (41 days) were found to bear flowers for longer duration.